Expression of Hexokinase in Stomata of Citrus Fruit Reduces Fruit Transpiration and Affects Seed Development - Lugassi, Nitsan; Kelly, Gilor; Arad, Tal; Farkash, Chagai; Yaniv, Yossi; Yeselson, Yelena; Schaffer, Arthur A.; Raveh, Eran; Granot, David; Carmi, Nir (Frontiers in Plant Science, 2020)
The temporal formation and spatial distribution of stomata on the surface of citrus floral organs and, specifically, on the ovule from which the fruit develops, were analyzed using GCGFP citrus plants that express GFP under the guard cell-specific KST1 promoter. Stomata are found on the style, sepal, and anther of the closed flower and on ovules from the stage of anthesis. It has previously been shown that HXK mediates sugar-sensing in leaf guard cells and stimulates stomatal closure. The activity and response of citrus fruit stomata to sugar-sensing by HXK was examined using GCHXK plants that express hexokinase (HXK) under the KST1 promoter. The transpiration of young green GCHXK citrus fruits was significantly reduced, indicating that their stomata respond to sugar similar to leaf stomata. Toward fruit maturation, fruit stomata are plugged and stop functioning, which explains why WT and GCHXK mature yellow fruits exhibited similar water loss. Seeds of the GCHXK plants were smaller and germinated more slowly than the WT seeds. We suggest that the stomata of young green citrus fruits, but not mature yellow fruits, respond to sugar levels via HXK and that fruit stomata are important for proper seed development.